The common country assessment, Bangladesh. - United Nations (Dhaka : Published for the United Nations [by] University Press, 2000)
A joint exercise by UN agencies in Bangladesh to assess the development situation of the country.
Includes bibliographical references (pages [147]-152).
BIED
Complimentary copy from BIED, Donated By Akbar Ali Khan (38673)
Keywords: United Nations -- Bangladesh; Economics; Bangladesh; Bangladesh -- Economic conditions; Bangladesh -- Social conditions